KARAKTERISTIK NATA DE PINA DENGAN PENAMBAHAN EKSTRAK TAUGE (Phaseolus radiatus) (Suara UNJA, 2025)
This research was conducted to determine the effect of adding mung bean sprout extract on the characteristics and organoleptic properties of nata de pina, as well as to identify the best concentration of mung bean sprout extract for its production. The study used a Completely Randomized Design (CRD) method with six treatment levels and three replications, consisting of adding mung bean sprout extract at concentrations of 25%, 30%, 35%, 40%, 45%, and 50%. The data obtained were statistically analyzed using Analysis of Variance (ANOVA), and if significant differences were found, Duncan's New Multiple Range Test (DNMRT) at a 5% significance level was applied. The observed parameters included yield, thickness, moisture content, crude fiber content, texture, and organoleptic properties (color, taste, texture, aroma, and overall acceptance). The organoleptic test was carried out with 25 semi-trained panelists. The results showed that the addition of mung bean sprout extract significantly affected the yield, thickness, crude fiber content, texture, and organoleptic tests for color, texture, and overall acceptance, but had no significant effect on moisture content, and the organoleptic tests for taste and aroma. The best treatment was found with the addition of 50% mung bean sprout extract, producing nata de pina with characteristics of yield (29.62%), thickness (20.20 mm), moisture content (96.91%), crude fiber content (7.03%), texture (10,404.60 gf), and organoleptic scores for color 2.60 (slightly white), taste 3.48 (bland), texture 3.08 (slightly chewy), aroma 3.60 (not sour-smelling), and overall acceptance 3.72 (somewhat liked).